1995
DOI: 10.1209/0295-5075/29/3/006
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Isotope Effect of Diffusion in a Metallic Glass

Abstract: The isotope effect E = d ln(D)/d In ( l / f i ) of CO diffusion in structurally relaxed CoS6Zrl4 and CoslZrlg glasses has been measured by means of a radiotracer technique. Within experimental accuracy no isotope effect was detected ( E < 0.04). This suggests a highly cooperative diffusion mechanism. The connection between diffusion and collective low-frequency relaxations in glasses is discussed.have been shown to be in conflict with a defect mechanism (see, e.g., [SI).Recently, we have succeeded in measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 29 publications
4
30
0
Order By: Relevance
“…Measuring the isotope effect it has been shown that diffusion in metallic glasses is via collective motion involving numbers of particles similar to our results. 50,54 In the liquid state, upon cooling towards the glass transition, the distribution of the atomic mean square displacements deviates increasingly from a Gaussian distribution, in agreement with earlier simulations. 74 The ''rapid quench values'' for the glassy state show for sufficiently long observation times a further increase upon cooling.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Measuring the isotope effect it has been shown that diffusion in metallic glasses is via collective motion involving numbers of particles similar to our results. 50,54 In the liquid state, upon cooling towards the glass transition, the distribution of the atomic mean square displacements deviates increasingly from a Gaussian distribution, in agreement with earlier simulations. 74 The ''rapid quench values'' for the glassy state show for sufficiently long observation times a further increase upon cooling.…”
Section: Discussionsupporting
confidence: 88%
“…Such a mechanism was, e.g., postulated for Hf diffusion in amorphous Ni 54 Zr 46 where, from pressure experiments, an activation volume for diffusion of the order of the atomic volume was deducted 47 similar to earlier results for Co diffusion. 48 The opposite result was found for Co in Co 81 Zr 19 where this mechanism was ruled out due to the vanishing activation volume.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Besides, the isotope effect of ion diffusion in a solid has been much investigated. [10][11][12][13][14][15][16] The isotope effect of lithium ion in lithium borate glasses or lithium metal has been reported. [17][18][19][20][21][22] The temperature dependence of the diffusion coefficient D of atoms ͑of mass m͒ diffusing by a simple vacancy mechanism in a solid is expressed by the Arrhenius equation…”
mentioning
confidence: 99%
“…Whereas the activation volumes of the order of an atomic volume have been taken as evidence of diffusion via thermally generated defects, the almost vanishing activation volumes allow one to rule out any diffusion mechanism similar to vacancy diffusion in crystalline solids. In accord with very small isotope effects of Co self-diffusion [13] and results from molecular dynamics simulations [14,15], the vanishing activation volumes were attributed to a direct highly collective diffusion mechanism that does not involve thermal defects [2, 6,13].…”
mentioning
confidence: 88%